Promoter-Based Integration in Plant Defense Regulation. Issue 4 (28th October 2014) - Li, Baohua; Gaudinier, Allison; Tang, Michelle; Taylor-Teeples, Mallorie; Nham, Ngoc T.; Ghaffari, Cyrus; Benson, Darik Scott; Steinmann, Margaret; Gray, Jennifer A.; Brady, Siobhan M.; Kliebenstein, Daniel J.
Abstract : An extensive transcriptional regulatory network modulates plant defense chemistry . Abstract: A key unanswered question in plant biology is how a plant regulates metabolism to maximize performance across an array of biotic and abiotic environmental stresses. In this study, we addressed the potential breadth of transcriptional regulation that can alter accumulation of the defensive glucosinolate metabolites in Arabidopsis ( Arabidopsis thaliana ). A systematic yeast one-hybrid study was used to identify hundreds of unique potential regulatory interactions with a nearly complete complement of 21 promoters for the aliphatic glucosinolate pathway. Conducting high-throughput phenotypic validation, we showed that >75% of tested transcription factor (TF ) mutants significantly altered the accumulation of the defensive glucosinolates. These glucosinolate phenotypes were conditional upon the environment and tissue type, suggesting that these TF s may allow the plant to tune its defenses to the local environment. Furthermore, the pattern of TF /promoter interactions could partially explain mutant phenotypes. This work shows that defense chemistry within Arabidopsis has a highly intricate transcriptional regulatory system that may allow for the optimization of defense metabolite accumulation across a broad array of environments.